Derivation of the Ångström Exponent Using Images Provided by a Low-Cost Digital Consumer Camera - Wagner, Frank (2010)
The Ångström exponent (AE) is a characteristic property of atmospheric aerosol particles. It is usually derived from columnar integrated measurements of instruments such as sun photometers or satellites. In contrast, the retrievals of the AE from horizontal path averaging measurements are rare. The objective of this work is to obtain the AE on a horizontal path based on images taken by a digital low-cost consumer camera.